2023
DOI: 10.1007/s12325-023-02590-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Clinical Implications of Individual Patient Characteristics and Treatment Choice on the Risk of Exacerbation in Asthma Patients with Moderate–Severe Symptoms

Dave Singh,
Sean Oosterholt,
Ian Pavord
et al.

Abstract: Introduction The assessment of future risk has become an important feature in the management of patients with asthma. However, the contribution of patient-specific characteristics and treatment choices to the risk of exacerbation is poorly understood. Here we evaluated the effect of interindividual baseline differences on the risk of exacerbation and treatment performance in patients receiving regular maintenance doses of inhaled corticosteroids (ICS) or ICS/long-acting beta-agonists (LABA) combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Moreover, baseline ACQ-5 was derived from ACT scores for patients included in studies ADA109055 and ADA109057. This was required because only ACT was recorded in these studies and ACQ-5 has been identified as a covariate affecting exacerbation risk and individual symptom trajectories during the course of treatment [ 5 , 20 ]. Conversion was performed considering the symptom category and percentiles of the scores of each scale.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, baseline ACQ-5 was derived from ACT scores for patients included in studies ADA109055 and ADA109057. This was required because only ACT was recorded in these studies and ACQ-5 has been identified as a covariate affecting exacerbation risk and individual symptom trajectories during the course of treatment [ 5 , 20 ]. Conversion was performed considering the symptom category and percentiles of the scores of each scale.…”
Section: Methodsmentioning
confidence: 99%
“… Recommended options: It is recommended to use a daily fixed-dose combination of low-dose ICS/LABA with an as-needed reliever for symptom relief (Evidence A). [ 87 128 129 130 ] Reliever therapy is recommended in the form of SABA (with or without ICS) whenever a maintenance fixed-dose combination of ICS/non-formoterol LABA or in the form of ICS/formoterol whenever a maintenance fixed-dose ICS/formoterol combination is prescribed. [ 131 132 ] Physicians should ensure the adherence of patients to this regimen[ 106 ] Alternative options: The addition of LTRA to a low-dose ICS is another option, especially in patients with concomitant rhinitis (Evidence A)[ 133 134 135 ] Continuation of ICS as a monotherapy by increasing the dose to the medium level is generally a less effective strategy (Evidence A).…”
Section: Section 6: Pharmacological Management In Adults and Adolescentsmentioning
confidence: 99%
“…Recommended options: It is recommended to use a daily fixed-dose combination of low-dose ICS/LABA with an as-needed reliever for symptom relief (Evidence A). [ 87 128 129 130 ] Reliever therapy is recommended in the form of SABA (with or without ICS) whenever a maintenance fixed-dose combination of ICS/non-formoterol LABA or in the form of ICS/formoterol whenever a maintenance fixed-dose ICS/formoterol combination is prescribed. [ 131 132 ] Physicians should ensure the adherence of patients to this regimen[ 106 ]…”
Section: Section 6: Pharmacological Management In Adults and Adolescentsmentioning
confidence: 99%